THE EFFECT OF TRADE OPENNESS ON POVERTY IN NIGERIA - Benedict Azu; Onyemaechi Ugboh (International Studies Journal)
This study examines the effect of trade openness on poverty in Nigeria. The study adopts autoregressive distributed lag (ARDL) model to study the relationship between poverty and trade openness and other explanatory variables. Measures of poverty used for this study were per capita income and human development index. Consequently, two autoregressive models were specified and estimated in order to examine the effect of trade openness on these two measures of poverty. In the two models, trade related variables (exchange rate and foreign direct investment) were included in the model as explanatory variables along with trade openness which is the key explanatory variable in the two models. The result of the analysis shows that in the first model trade openness has significant positive effect on per capita income only in the long run, foreign direct investment has a positive effect on per capita income both in the long run and in the short run while exchange rate has a negative effect on per capita income in the short run. In the second model, trade openness does not have a significant effect on human development, foreign direct investment has a significant and positive effect on human development while exchange rate has a significant negative effect on human development. It is recommended that the government should ensure that trade policies are mutually beneficial to Nigeria and the trading partner and that some specific bilateral trade relations are well negotiated. It is also recommended that the government should create the enabling environment to attract foreign direct investment into the Nigerian economy because of the positive gains on poverty reduction as shown in the findings.